Perception of safety in transport use among traders in South Western Nigeria: A case study of Osogbo, Osun State - Shima-kohol , Adenike; Adeniyi , Oluwakoya (Corpus Intellectual, 2024)
Studies in global literature have shown gender disparity in the perception of safety and security issues. Its effects on mobility, in particular, have been profound, leading to a dramatic change in travel patterns and changes in the selection and utilisation of modes of transportation. Inequalities across population groups have also been compounded by the effects on the social and economic arenas, with women being one of the most affected groups, which may increase the already well-known gender gap in mobility. This study aims to examine the perception of safety and insecurity among male and female traders, most especially in the use of public and private transport systems in the medium-sized city of Osogbo, Nigeria, with a significant focus on prominent markets in the town. The study used qualitative and quantitative survey methods—data collected wasanalysed using an Independent t-test and personal interview. Valuable suggestions on how to address mobility inequalities and insecurity amongst traders in urban locations were given.